2013
DOI: 10.1097/mao.0b013e31829561b6
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Accuracy Evaluation of Image-Guided Robot System for Direct Cochlear Access

Abstract: The purpose-built robot system was able to perform a safe and reliable DCA for cochlear implantation. The workflow implemented in this study mimics the envisioned clinical procedure showing the feasibility of future clinical implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
87
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 16 publications
1
87
0
Order By: Relevance
“…After immobilization of the animal's head using a pin type head-clamp, a high-accuracy image-guided surgical robot system (12,22,29,30) was used to drill to each of the predefined measurement points in the planned trajectories (see Video, Supplemental Digital Content 1, http://links.lww.com/MAO/ A345, which shows how the image-guided robotic system drills to the next measurement point). Upon reaching a given measurement position, the drill was removed, and to ensure good electrical contact between electrodes and bony tissue, irrigation (NaCl, 0.9%) was applied.…”
Section: Drilling and Facial Nerve Stimulation Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…After immobilization of the animal's head using a pin type head-clamp, a high-accuracy image-guided surgical robot system (12,22,29,30) was used to drill to each of the predefined measurement points in the planned trajectories (see Video, Supplemental Digital Content 1, http://links.lww.com/MAO/ A345, which shows how the image-guided robotic system drills to the next measurement point). Upon reaching a given measurement position, the drill was removed, and to ensure good electrical contact between electrodes and bony tissue, irrigation (NaCl, 0.9%) was applied.…”
Section: Drilling and Facial Nerve Stimulation Measurementsmentioning
confidence: 99%
“…Recently, two studies (11,12) have demonstrated sufficient end-to-end image-guided drilling accuracies of 0.31 AE 0.1 and 0.15 AE 0.08 mm using templates and a robotic guidance respectively, suggesting their potential clinical implementation. The minimally invasive approach is based on the creation of a small diameter tunnel (1.5-2 mm) from the surface of the patient's mastoid to the cochlea following a preoperatively planned path through the facial recess.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure, which involves the drilling of a direct tunnel from the mastoid surface to the middle ear cavity relies on image guidance to ensure structure preservation. Up to date, there is no established minimally invasive procedure, but an image guided surgical robot [7], developed at the university of Bern, has demonstrated sufficient accuracy in ex vivo experiments (less than 0.15 ± 0.08mm [6]) to allow precise drilling of the tunnel without damaging close lying anatomy.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] Another proposed method utilized a self-developed and constructed robot to drill along a specified path, by which high resolution surgery could be achieved. [7,8] Registration is an important aspect of surgical navigation resolution. However, due to the registration of the navigation system, the infliction of additional trauma cannot be ignored in the above two approaches.…”
Section: Introductionmentioning
confidence: 99%